On the interplay between astrophysical and laboratory probes of MeV-scale axion-like particles - Fatih Ertas; Felix Kahlhoefer (Journal of High Energy Physics, 2020)
Abstract Studies of axion-like particles (ALPs) commonly focus on a single type of interaction, for example couplings only to photons. Most ALP models however predict correlations between different couplings, which change the phenomenology in important ways. For example, an MeV-scale ALP coupled to Standard Model gauge bosons at high energies will in general interact with photons, W ± and Z bosons as well as mesons and nucleons at low energies. We study the implications of such scenarios and point out that astrophysical constraints, in particular from SN1987A, may be substantially relaxed, open- ing up new regions of parameter space that may be explored with laboratory experiments such as NA62.